Comparison of Stand-alone Cage versus Intervertebral Cage with Pedicle Screw and Rod Fixation in Dogs with Degenerative Lumbosacral Stenosis - van den Brink, Eline J.C.; Kamali, Seyed A.; Tellegen, Anna R.; Meij, Björn P. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
The aim of this study was to assess the clinical outcome of treatment of degenerative lumbosacral stenosis in dogs with a stand-alone intervertebral spacer (S group) and combined with a pedicle screw and rod fixation (S + PSRF group) in the lumbosacral junction.Retrospective study. Medical records (2014–2023) were reviewed for dogs treated with a stand-alone intervertebral spacer (S group) or a spacer combined with PSRF (S + PSRF group). Data collected included clinical signs at the time of presentation, surgical technique, implant type, perioperative bacterial culture, complications, outcomes and subsidence.Minor complications occurred in 10/11 dogs in the S group and 6/17 dogs in the S + PSRF group. Major complications occurred in 3/11 dogs in the S group and 5/17 dogs in the S + PSRF group. Long-term outcome was excellent in 63.6% dogs in the S group and 64.7% dogs in the S + PSRF group. Subsidence was noted in 75% of the cases in the S group compared with 33% of cases in the S + PSRF group. Bacterial cultures were positive in 6/28 cases.Both treatment options were associated with full return of function in 64 to 65% of cases. Complications were more frequent in the S group. The S + PSRF group showed less subsidence of the cage. There was more frequent evidence of bone ingrowth in the intervertebral spacer in the S + PSRF group. Based on the observations in this study, both treatment options are viable for the treatment of degenerative lumbosacral stenosis with similar long-term outcomes; however, S + PSRF may result in less subsidence and better fusion and may therefore be preferable.
Keywords: dog; lumbosacral stenosis; pedicle screw and rod fixation; lumbosacral fusion